Low‐Temperature‐Processed Printed Metal Oxide Transistors Based on Pure Aqueous Inks. (3rd March 2017) - Scheideler, William J.; Kumar, Rajan; Zeumault, Andre R.; Subramanian, Vivek
Abstract : Additive patterning of transparent conducting metal oxides at low temperatures is a critical step in realizing low‐cost transparent electronics for display technology and photovoltaics. In this work, inkjet‐printed metal oxide transistors based on pure aqueous chemistries are presented. These inks readily convert to functional thin films at lower processing temperatures ( T ≤ 250 °C) relative to organic solvent‐based oxide inks, facilitating the fabrication of high‐performance transistors with both inkjet‐printed transparent electrodes of aluminum‐doped cadmium oxide (ACO) and semiconductor (InO x ). The intrinsic fluid properties of these water‐based solutions enable the printing of fine features with coffee‐ring free line profiles and smoother line edges than those formed from organic solvent‐based inks. The influence of low‐temperature annealing on the optical, electrical, and crystallographic properties of the ACO electrodes is investigated, as well as the role of aluminum doping in improving these properties. Finally, the all‐aqueous‐printed thin film transistors (TFTs) with inkjet‐patterned semiconductor (InO x ) and source/drain (ACO) layers are characterized, which show ideal low contact resistance ( R c < 160 Ω cm) and competitive transistor performance ( µ lin up to 19 cm 2 V −1 s −1, Subthreshold Slope (SS) ≤150 mV dec −1 ) with only low‐temperature processing ( T ≤ 250 °C). Abstract : High‐mobility inkjet‐printed transistors with transparent electrodes are fabricated at below 250 °C exclusively via aqueous ink chemistries. Intrinsic aqueous fluid properties lead to enhanced printing fidelity, high electrical performance, and better ambient stability relative to organic inks. Degenerately doped transparent conductors (CdO:Al) are developed as a low resistance inkjet‐printed contact to an aqueous‐printed InO x semiconductor.